2017
DOI: 10.1155/2017/6426747
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis Characterization and Biological Activities of Coordination Compounds of 4-Hydroxy-3-nitro-2H-chromen-2-one and Its Aminoethanoic Acid and Pyrrolidine-2-carboxylic Acid Mixed Ligand Complexes

Abstract: Coordination compounds of 4-hydroxy-3-nitro-2H-chromen-2-one and their mixed ligand complexes with aminoethanoic acid and pyrrolidine-2-carboxylic acid were synthesized by the reaction of Cu(II) and Zn(II) salts in molar ratio 1 : 2 for the coumarin complexes and 1 : 1 : 1 for the mixed ligand complexes, in basic media. The compounds formed were characterized using infrared, Uv-vis spectrophotometric analyses, mass spectrometry, magnetic susceptibility measurements, and EDX analyses. It was concluded that 4-hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 52 publications
(88 reference statements)
1
14
0
Order By: Relevance
“…Although there are a number of anti-inflammatory drugs currently in the market, however, they exhibit significant adverse effects. In this respect, coordi-nation chemistry may be deemed as a useful tool in curbing this [36] [37] [38] [39]. Earlier investigations have revealed that coordination of metal ions to biologically active agents may improve their efficiency and bioavailability and in some cases, reduce their well-recognized side effects [36] [37] [38] [39].…”
Section: Introductionmentioning
confidence: 99%
“…Although there are a number of anti-inflammatory drugs currently in the market, however, they exhibit significant adverse effects. In this respect, coordi-nation chemistry may be deemed as a useful tool in curbing this [36] [37] [38] [39]. Earlier investigations have revealed that coordination of metal ions to biologically active agents may improve their efficiency and bioavailability and in some cases, reduce their well-recognized side effects [36] [37] [38] [39].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, one present strategy in the field of pharmacological research is coordinating 1,10-phenanthroline with transition metal ions to make its nitrogen atoms unavailable for denaturation [ 12 15 ]. Furthermore, this activity enhances the medicinal activity of transition metal complexes [ 16 , 17 ]. Based on this, many transition metal complexes of 1,10-phenanthroline have been found exhibiting numerous biological activities such as antiviral [ 18 , 19 ], anti-inflammatory, antitumor [ 20 ], anti-Candida [ 21 ], antimycobacterial [ 22 ], and antimicrobial [ 23 ] activity upon binding to DNA.…”
Section: Introductionmentioning
confidence: 99%
“…This is because these compounds have shown significant potential in the production of therapeutic products. They are known for a variety of uses: physiological, antimicrobial 1,2 , antioxidant 3,5 , anti-inflammatory 6,7 , anticoagulant and antitumor 8 activities. In recent years, there is much attention in the search for antioxidants from natural, industrial sources.…”
Section: Introductionmentioning
confidence: 99%